How expressive ties energize competitive performance in DanceSport dyads: unraveling the role of athlete engagement in an innovatively applied actor-partner interdependence mediation model - Liu, Xiuxia; Liu, Yang; Pan, Dandan; Weng, Xinghe (Frontiers in Psychology, 2024)
This study explores the significant impact of expressive ties (EI) between DanceSport couples on their competitive performance (CP). Utilizing a dyadic approach, we examined the performance achievement processes of DanceSport couples in relation to their EI. Participants comprised 67 dyads of Chinese elite dancers aged between 16 and 30 years. The dyadic analysis was carried out using a structural equation model based on the actor-partner interdependence mediation model. The results showed that, with regard to actor effects, both male (β=0.292, P=0.012) and female (β=0.443, P<0.001) dancers' perceived quality of EI had a positive correlation with CP. The males' athlete engagement (AE) partially mediated the impact of EI on CP [indirect effect=0.144, SE=0.072, 95% confidence intervals (CI)=0.020, 0.283]. Regarding partner effects, females' perceived EI quality positively influenced the male's CP (β=0.26, P=0.023) and mediated this association through the male's AE [indirect effect=0.086, SE=0.041, 95% confidence intervals (CI)=0.003, 0.149]. Similarly, the females' AE mediated the effect of males' perceived EI quality on the females' CP [indirect effect=0.152, SE=0.074, 95% confidence intervals (CI) =0.002, 0.256]. Through this, we not only validated the propositions of the self-determination theory but also provided valuable insights to further enrich it. Our findings underscore that self-determination theory must account for individual gender characteristics.